Polinização entomófila em pomares comerciais de maçã na Região Sul do Brasil - Ramos, Jenifer Dias (2016)
Pollination is an important ecosystem service responsible for the production and quality of 33% of agricultural crops. In the agricultural context, the bees are the main pollinators, and Apis mellifera, the main species managed for pollination of crops. Among these it highlights the cultivation of apple, which is a species that has many varieties with a high degree of incompatibility, requiring the presence of “pollinazier” varieties of calls in the orchards, which provide pollen for cross-pollination.The apple planting system usually in Brazil consists of alternating rows of the commercial cultivar with lines of the "pollinator" cultivar, being common the use of Apis mellifera colonies to ensure cross-pollination. This thesis is divided into two papers, the first entitled "Evaluation of apple trees planting systems with respect to the pollinaton performance of Apis mellifera" whose objective was to evaluated the efficiency of two planting systems with respect to the pollination performance of Apis mellifera. The study was conducted in an 'Gala' apple orchard that presented two planting systems: (1) conventional, consisting of three lines of the commercial cultivar ('Gala') and two rows of the “pollinizer” cultivar ('Fuji'); (2) planting with ‘crab-apples’, which consists in planting wild apple trees every six meters in the line of the commercial cultivar. Fruis from these systems were analysed in relation to weight, seed number and distribution among carpels. We followed 121 bees during foraging flight: 14% of them crossed between the lines of the orchard and 94% collected nectar. There was correlation between fruit weight and number of seeds, and the fruits of the’ crab-apple’ system had more seeds (6 ± 2) than the fruit of conventional system (5 ± 2). These results indicate that the planting system with ‘crab-apples’ is better considering the foraging behavior of honey bees. The second article entitled "Attractiveness of floral resources of apple to Apis mellifera" whose objective was to compare the offer of floral resources between cultivars of Malus domestica 'Fuji ', 'Fuji Suprema ', ' Gala' and ' Imperial Gala' and to evaluate the visitation rate of Apis mellifera. In a collection orchard it were evaluated the floral abundance, the nectar volume and its soluble solids content (Brix) and the number of pollen grains per flower for the four varieties. Besides this, in an experimental orchard, the visitation rate of Apis mellifera in ‘Fuji’ and ‘Gala’ was verified and a linear mixed model calculated to verify which cultivar was the most attractive. ‘Gala’ was the most attractive for the bees, presenting higher abundance of flowers, volume of nectar and amount of pollen grains per flower. Comparing the flower resources of all cultivars, ‘Imperial Gala’ can be considered the most attractive. was to compare the offer of floral resources between cultivars of Malus domestica 'Fuji ', 'Fuji Suprema ', ' Gala' and ' Imperial Gala' and to evaluate the visitation rate of Apis mellifera. In a collection orchard it were evaluated the floral abundance, the nectar volume and its soluble solids content (Brix) and the number of pollen grains per flower for the four varieties. Besides this, in an experimental orchard, the visitation rate of Apis mellifera in ‘Fuji’ and ‘Gala’ was verified and a linear mixed model calculated to verify which cultivar was the most attractive. ‘Gala’ was the most attractive for the bees, presenting higher abundance of flowers, volume of nectar and amount of pollen grains per flower. Comparing the flower resources of all cultivars, ‘Imperial Gala’ can be considered the most attractive.